Character Development of the Main Character in Edgar Allan Poe’s Selected Short Stories - Ermina, Yeni; Natsir, Muhammad; Muhajir, Fatimah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
In literary works, characters undergo significant changes in their life. Some aspects influenced the changes personality of the characters. One of the literary works that showed this situation is a short story by Edgar Allan Poe. The researcher analyzed the main character of each short story from Edgar Allan Poe. They are The Black Cat, The Tell-Tale Heart, and William Wilson. This research aimed to find the characterization and personality development of the main character in Poe’s selected short stories. Hence, the researcher used Kenan’s characterization theory and Hurlock’s personality development. This research used qualitative research design and content analysis study as an approach. The researcher found the characteristics of the main character: sensitive, impulsive, uncontrollable behavior, easily tempered, insane, anxious and stubborn. Those are presented through indirect characterizations: action, external appearance, and environment. From the characterization, the main character in Poe’s selected short stories changed from good to bad, affecting character changes. In the first short story, The Black Cat, the personality development happened because the character “I” was influenced by alcohol. In the second short story, The Tell-Tale Heart, the personality development happened because the “I” character got irritated by the old man’s eye. In the third short story William Wilson, the personality development happened because William was influenced by his environment, which is a significant influence as he got ignored by his family.